Creative Economy in the Republic of Sakha (Yakutia) - Mikhaylova, Anna (KnE Social Sciences, 2021)
The article is devoted to the analysis of the concept of a new creative economy. Creative economy is a special sector of the economy, combining activities related to intellectual work, creativity. The creative economy is based on intellectual work, generating income not only from the final product created, but also from trading in its results and intellectual property rights as opposed to traditional factors of production. In the creative economy, the kreatosphere is formed. The kreatosphere is a type of activity in the creative economy. Features of the products of the creative economy are the high added values created by intellectual effort. On the example of the Republic of Sakha (Yakutia), accelerators of the development of the kreatosphere are highlighted: the development of educational programs, the preparation of creative, creative-minded specialists; support of innovation centers and investments in creative industries; development of creative projects. Keywords: new economy, creative economy, digital economy, kreatosphere, creative class, creativity